Facile Fabrication of Tumor Redox‐Sensitive Nanoassemblies of Small‐Molecule Oleate Prodrug as Potent Chemotherapeutic Nanomedicine. Issue 46 (30th September 2016) - Luo, Cong; Sun, Jin; Sun, Bingjun; Liu, Dan; Miao, Lei; Goodwin, Tyler Jay; Huang, Leaf; He, Zhonggui
Abstract : The conjugate of paclitaxel (PTX) and docosahexaenoic acid has entered into clinical trials. However, the most recent clinical outcomes fell short of expectations, due to the extremely slow drug release from the hydrophobic conjugates. Herein, a novel prodrug‐based nanoplatform self‐assembled by the disulfide bond linked conjugates of PTX and oleic acid for rapid and differential release of PTX in tumor cells is reported. This redox‐responsive prodrug‐nanosystem demonstrates multiple therapeutic advantages, including one‐step facile fabrication, high drug‐loading efficiency (56%, w/w), on‐demand drug release responding to redox stimuli, as well as favorable cellular uptake and biodistribution. These advantages result in significantly enhanced antitumor efficacy in vivo, with the tumor almost completely disappearing in mice. Such a uniquely engineered prodrug‐nanosystem has great potential to be used as potent chemotherapeutic nanomedicine in clinical cancer therapy. Abstract : To bridge the gap between hydrophobic lipid prodrugs of paclitaxel and favorable antitumor efficacy, a smart redox‐sensitive prodrug‐nanosystem has been designed. The uniquely engineered stimulus‐responsive prodrug nanoassemblies, with high drug loading (over 50%, w/w), on‐demand drug release within tumor cells, and potent antitumor efficacy, hold great potential to be used as a promising chemotherapeutic nanomedicine in cancer therapy.